Advancing Climate Transition through Fiscal Tools: The Role of Carbon Taxation and Fuel Subsidy Reform - Zayed, Farah Amgad (AUC Knowledge Fountain, 2026)
This study highlights how fiscal policy tools can accelerate Egypt's climate transition, with emphasis on carbon taxes and fossil fuel subsidies reforms. It investigates how fiscal tools can reduce carbon emissions and promote economic development by primarily relying on qualitative interviews with policymakers, consultants, representatives of the private sector, and civil society actors, paralleled with some descriptive and comparative analysis. The results show that even though Egypt has made significant strides in advancing green transition, including updating the Nationally Determined Contributions (NDC), introducing the first African Voluntary Carbon Market (VCM), as well as phasing out fossil fuel subsidies gradually, institutional coordination, governance readiness, and social acceptance are still major challenges. According to the findings, fiscal policies, alone are insufficient in the absence of supportive policy reforms and enabling regulatory measures that support green transitions. The findings draw attention to the importance of a strong Monitoring, Reporting, and Verification (MRV) framework in this context to evaluate the success of fiscal reforms, boost investor confidence, and guarantee compliance with global commitments and obligations. International binding treaties such as the Paris Agreement urges signatory countries, to set and implement Nationally Determined Contributions (NDCs) to advance their climate agendas. Other trade instruments such as Carbon Border Adjustment Mechanism (CBAM) represents global market pressures that drive Egyptian exporters to adapt to maintain competitiveness in EU markets. The study suggests a gradual fiscal reform plan that gradually eliminates inefficient subsidies, implements carbon pricing, and reallocates funds to accelerate the adoption of green energy solutions in key sectors such as energy and transport.